Optimalisasi distribusi Ruang Terbuka Hijau (RTH) Di Kelurahan Banta-Bantaeng kecamatan Rappocini kota Makassar - Nashrah Arsyad (LOSARI : Jurnal Arsitektur Kota dan Pemukiman, 2017)
The ideal area of Green Open Space (RTH) is at least 30% of the area of urban areas. However, in reality, the availability of Green Open Space inalmost all cities in Indonesia only reaches 10% of the area on average. The limited availability of Green Open Space and the uneven distributionand concentration of green open space at certain points in several areas result in unequal growth and development of the city and tend to be chaotic. This study aims to identify the availability of Green Open Space and to analyze the optimization of the distribution of green Open Spaceaccording to its type and function in Makassar City. This research was carried out in Makassar City by taking the study location in Banta-bantaeng Village, Rappocini District, Makassar City, with the research time starting from July 2016 to April 2017. The methods used in this studyare qualitative descriptive methods and quantitative descriptive methods. The qualitative descriptive method was used to identify the availabilityof the types and functions of Green Open Space while the quantitative descriptive method was used to describe the need and distribution of greenopen space in Makassar City through the calculation of simple mathematical formulas and projections of the number of population. The results ofthis study show that the availability of green open space in Makassar City, especially in Banta-bantaeng Village, has not met the standard of green open space needs reviewed from the area and the number of population. The results of this study also show that the distribution of open space hasnot been optimally distributed, among other things, due to the limited free space in several areas of Banta-bantaeng Village caused by denseresidential areas